Characterization, Pre-treatment and Valorization of Pineapple Peels - Dalal, Eshmit (My University, 2023)
The pineapple (Ananas comosus), a fruit that is in high demand all over the world, produces a lot of waste in the agro-industrial sectors, particularly pineapple peels. The key qualities of pineapple peels as a feedstock for the manufacture of fermentable sugars that might be utilized for ethanol production led to waste valorization. Various nutrient estimations and other characterizations were analyzed for the dried pineapple peel powder, the results of which showed that the dried pineapple peel powder (DPPP) would be a potential feedstock for the enhancement of sugar production. For these, three different pre-treatments were chosen, which were steam explosion, hot water, and ultrasonication pre-treatment. After which, characterizations like XRD, TGA, and SEM were performed for the pre-treated samples in comparison to the dried pineapple peel powder to analyze thermal stability, structural morphology, and functional group changes. Therefore, it was analyzed that sugar concentrations were enhanced along with other nutrients like phenolic content, starch, and amino acids, which can be valorized further for bioethanol production. Lastly, we concluded that the techniques which we used in this study can give rise to the low-cost and environment-friendly ways to produce beneficial fermentable sugars from pineapple fruit peel wastes, which are necessary for the production of ethanol from the dried pineapple fruit peel waste.
Keywords: Pineapple peels; Ultrasonic pre-treatment; Value added product; Hot water pre-treatment; Fermentable sugars